ENVIRONMENTAL IMPACT ASSESSMENT IN CIVIL ENGINEERING FOR SUSTAINABLE INFRASTRUCTURE PROJECTS - Dery Mochamad (RADJA PUBLIKA, 2025)
Environmental Impact Assessment (EIA/EIA) is an important instrument in civil engineering infrastructure project planning to ensure that development runs in line with sustainability principles. This study aims to examine the extent to which the implementation of EIA in civil engineering projects in Indonesia has accommodated environmental and social sustainability aspects. With a descriptive qualitative approach, data was collected through interviews, observations, and documentation studies of several major infrastructure projects. The results show that the implementation of EIA is generally still procedural and has not been fully integrated in the technical design of the project. The aspects of community participation and ecological sustainability are often ignored or implemented in a formality. On the other hand, projects with high public involvement and proper utilization of environmental technologies show better quality of EIA documents. This study suggests the importance of increasing the capacity of actors, integrating EIA from the early stages of planning, and strengthening supervision of the implementation of RKL-RPL. With this strengthening, EIA can play a strategic role in realizing infrastructure that is not only functional and economical, but also environmentally and socially friendly.